Effect of hematopoietic stem cell on tumor necrosis factor- α expression, spiral artery remodeling and placental apoptosis in lead-exposed pregnant mice - Widjiati; Suryo Kuncorojakti; Hendy Hendarto; Viski Fitri Hendrawan; Aulanni'am Aulanni'am (Asian Pacific Journal of Reproduction, 2017)
Objective: To evaluate the effectiveness of hematopoietic stem cell (HSC) on TNF-α expression, spiral artery remodeling, and placental apoptosis.Methods: The study used pregnant mice divided to five groups of treatment: Group 1, without treatment; Group 2, 1/12 LD50 of lead and Aquadest; Group 3, 1/16 LD50 of lead and Aquadest, Group 4, 1/12 LD50 of lead and 1 × 107 HSC; and group 5, 1/16 LD50 of lead and 1 × 107 HSC. Histopathology examination was performed to identify spiral artery remodeling. Immunohistochemistry analysis was conducted to characterize TNF-α expression and the apoptosis index. The data from all five groups were compared using the ANOVA test.Results: TNF-α expression differed significantly among the groups that were not exposed to lead, exposed to lead and exposed to lead after HSC treatment (P<0.01). There was also a significant difference of spiral artery remodeling between groups without lead-exposed, lead exposed and lead exposed followed HSC treatment (P<0.05). In apoptosis index evaluation there was a significant difference between groups without lead-exposed, lead exposed and lead exposed followed HSC treatment, but not in the groups of 1/16 LD50 of lead followed HSC (P>0.05).Conclusions: In lead-exposed pregnant mice, the administration of hematopoietic stem cell may decrease TNF-α expression, spiral artery remodeling, and placental apoptosis index but in the group of 1/16 LD50 of lead and HSC treatment, apoptosis index has no differences with those of control group.